Pelatihan Metode Pembelajaran Project Based Learning Bagi Guru – Guru Bahasa Inggris di SMPN 2 Jati Agung, Lampung Selatan - Hartiwi, Juni; Sari Dewi, Nila; Pradana, Sandi (P3M STIT TANGGAMUS, 2023)
Pelatihan Metode Pembelajaran Project Based Learning Bagi Guru – Guru Bahasa Inggris di SMPN 2 Jati Agung, Lampung Selatan